The Design of Experiments in Occupational Ergonomics Research: Issues and Challenges. (November 2019) - Fox, Bob; Mines, Dan; Cort, Joel; Jones, Monica; Lu, Ming-Lun; Potvin, Jim; Rempel, David
As with all scientific disciplines involving research (laboratory or field), the design of an experiment, and the statistical methods used, are critical factors in research rigor, thus in our ability to compare, evaluate and communicate research findings. Courses in experimental design and statistics are required for the pursuit of advanced training in ergonomics. Across various scientific fields, there has been renewed interest in, and scrutiny of, statistical methods in establishing the validity and "truthfulness" of data, opinions, interpretations and projections of outcomes. Ergonomics researchers use distinct research methods (e.g., laboratory vs field; cross-sectional v. experimental, etc.) and must contend with a variety of constraints based on resources, availability of participants and access to the workplace. The variety of study designs chosen will challenge researchers as well as practitioners when comparing their results across published studies and attempting to generalize findings to new settings. This discussion panel will explore several the questions and issues related to research design and draw on specific studies from the literature. Topics and discussion will include study design (laboratory v field); different forms of experimental design (RCT v opportunistic); sample size and heterogeneity; non-parametric methods and differences in outcome measures and study durations. Following the presentations, ample time will be set aside for discussions of key issues with the panelists and audience. This session is relevant for the practitioners who must understand, interpret and apply the results of research to real-world problems.